The Chosen Few: Disproportionate Resource Use in Ventral Hernia Repair. Issue 8 (August 2013) - Poulose, Benjamin K.; Beck, William C.; Phillips, Sharon E.; Sharp, Kenneth W.; Nealon, William H.; Holzman, Michael D.
The objectives of this study were to determine if disproportionately small numbers of patients use more resources for ventral hernia repair (VHR) and to identify factors associated with this group. Patients undergoing VHR were identified using national 2009 Healthcare Cost and Utilization Project data. Mean total hospital charges (THCs) were calculated and patients were divided into high charges (HC, greater than 50% mean THC) and low charges (LC, 50% or less mean THC) groups. Multivariate analysis was used to identify factors associated with the HC group. We estimated 181, 000 hospitalizations for VHR in 2009 with mean THC of 54, 000. Fifteen per cent of patients comprised the HC group with 85 per cent in the LC group. The HC group had higher THC (173, 000 vs 32, 000; P < 0.05), increased mean length of stay (16.0 vs 4.1 days, P < 0.05), and higher mortality (6.3 vs 0.6%, P < 0.05). Risk factors for HC included congestive heart failure (odds ratio [OR], 2.2; 95% confidence interval [CI], 2.0 to 2.5), chronic lung disease (OR, 1.3; 95% CI, 1.2 to 1.4), Asian race (OR, 2.5; 95% CI, 1.7 to 3.7), nonelective operation (OR, 1.9; 95% CI, 1.6 to 2.3), and male gender (OR, 1.2; 95% CI, 1.1 to 1.3). For inpatient VHR, a remarkably small proportion of patients use disproportionately high hospital resources. The identified risk factors can help surgeons predict patients who are likely to consume large amounts of resources.